BIOEKOLOGI TUMBUHAN KETAPANG (Terminalia catappa) DI PANTAI KURANJI, KABUPATEN LOMBOK BARAT - Fitriani; Karmila Fajriah; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Ketapang (Terminalia catappa) is a coastal plant that plays an important role in maintaining the balance of the coastal ecosystem. This study aims to analyze the bioecological characteristics of Terminalia catappa on Kuranji Beach, West Lombok Regency. The method used was direct field observation by measuring environmental parameters such as soil temperature, soil pH, and soil moisture. The results of the study showed that the soil temperature was 35°C, soil pH 6.8, and soil moisture 1.5, indicating hot environmental conditions with low humidity levels. These conditions reflect the characteristics of a coastal ecosystem with limited water and high temperature. Nevertheless, Terminalia catappa is able to adapt well through supportive morphological structures and root systems, allowing it to continue growing in this environment. These findings indicate that Ketapang has a high level of resilience to coastal environmental conditions.